The views of teacher candidates on the handling of classes during the process of their pre-service education - Gökyer, Necmi (My University, 2012)
The aim of this study is to determine the views of teacher candidates on the handling of classes during their pre-service education. The population of the study is composed of 1208 students who have been going on their education in the second, third and fourth classes of different departments in the Education Faculty of Fi{dotless}rat University. The sample of the study consists of 552 students who were chosen via simple random sampling. In order to determine the views of the students, a data collection tool including 37 points has been developed. In the analysis of data, t test, one-way analysis of variance and LSD test have been done. According to research findings, the views of candidate teachers about both the instructors and themselves in the process of the subjects' handling during their pre-service education are in the level of 'I slightly agree'. The views of candidates who have been studying in the departments of Social Sciences Teaching, Science Teaching, Mathematics Teaching, Primary School Teaching and Turkish Teaching have been thinking more negatively about their instructors' way of handling the classes.
Ö?retmen adaylarinin hizmet öncesi e?itimleri sürecinde derslerin işlenişine ilişkin görüşleri
Keywords: Handling of classes; Instructors; Pre-service teacher training; Teacher candidate